The Authority of Execution by Court on the International Arbitration Decision - Zulhilmi Rizki Filhaj (Universitas Muhammadiyah Surabaya, 2020)
The winner of SIAC (Singapore International Arbitration Center) Number 062/08 made an Indonesian national legal effort, namely the application for recognition and implementation of international arbitration decisions as stipulated in article 65 of Act Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. However, after the application was registered with the Central Jakarta Court, it provided a decree which basically refused because the arbitration dispute was not included in the scope of the trade and violated public order. Because he received rejection of the recognition and implementation of the arbitration ruling from the Central Jakarta Court, the winner of the SIAC arbitration award filed an appeal to the Supreme Court Number 01 K / Pdt.Sus / 2010 whose result was justifying the previous Decision of the Central Jakarta Court and obtaining assertion that there was no even foreign powers can interfere with the ongoing legal process in Indonesia. This clearly violates public order, according to the Supreme Court ruling. Thus, the international arbitration award cannot get recognition and cannot be implemented in the Republic of Indonesia.Keywords: Supreme Court, International Arbitration, recognition and implementation of international arbitration